Breaking the sodium solubility limit for extraordinary thermoelectric performance in p-type PbTe. Issue 9 (12th August 2022) - Zhu, Yingcai; Hu, Lei; Zhan, Shaoping; Ina, Toshiaki; Gao, Xiang; Hong, Tao; Zhao, Li-Dong
Abstract : Sodium solubility is largely enhanced with the introduction of AgInSe2 in Pb1− y Na y Te matrixes, which facilitates band convergence, leading to an exceptional figure-of-merit ZT of ∼2.5 at 773 K in p-type PbTe. Abstract : The thermoelectric performance of a given material is closely related to its carrier concentration. However, the maximum solubility of dopants in matrixes is a key limitation for improving the carrier concentration, which may result in an underestimated figure-of-merit ZT . Here we show that Na solubility in the PbTe– x % AgInSe2 (LISST) system is largely enhanced exceeding its conventional solubility limit. The enhanced Na solubility facilitates band convergence corroborated by the Pisarenko relationship and temperature-dependent Hall coefficient measurements. Accordingly, we achieve a large power factor of ∼28.4 μW cm −1 K −2 at 873 K for Pb0.95 Na0.05 Te–0.5% AgInSe2 . In addition, the lattice thermal conductivity is suppressed with increasing Na content. Hence, the quality factor is largely boosted especially at high temperatures due to the enhanced weighted mobility and depressed lattice thermal conductivity. Consequently, an ultrahigh figure-of-merit ZT of ∼2.5 at 773 K and a large average ZT ( ZT avg ) of ∼1.5 at 323–873 K are achieved in Pb0.95 Na0.05 Te–0.5% AgInSe2 . Our findings demonstrate that a synergistic optimization of electrical and thermal properties can be realized through breaking the solubility limit of the doped component, providing a promising path for the enhancement of thermoelectric performance.